Clinical management of endoscopically resected pT1 colorectal cancer - Antonelli, Giulio; Berardi, Giammauro; Rampioni Vinciguerra, Gian Luca; Brescia, Antonio; Ruggeri, Maurizio; Mercantini, Paolo; Corleto, Vito Domenico; D’Ambra, Giancarlo; Pilozzi, Emanuela; Hassan, Cesare; Angeletti, Stefano; Di Giulio, Emilio (Endoscopy International Open, 2018)
Background Implementation of colorectal cancer (CRC) screening programs increases endoscopic resection of polyps with early invasive CRC (pT1). Risk of lymph node metastasis often leads to additional surgery, but despite guidelines, correct management remains unclear. Our aim was to assess the factors affecting the decision-making process in endoscopically resected pT1-CRCs in an academic center.Methods We retrospectively reviewed patients undergoing endoscopic resection of pT1 CRC from 2006 to 2016. Clinical, endoscopic, surgical treatment, and follow-up data were collected and analyzed. Lesions were categorized according to endoscopic/histological risk-factors into low and high risk groups. Comorbidities were classified according to the Charlson comorbidity index (CCI). Surgical referral for each group was computed, and dissociation from current European CRC screening guidelines recorded. Multivariate analysis for factors affecting the post-endoscopic surgery referral was performed.Results Seventy-two patients with endoscopically resected pT1-CRC were included. Overall, 20 (27.7 %) and 52 (72.3 %) were classified as low and high risk, respectively. In the low risk group, 11 (55 %) were referred to surgery, representing over-treatment compared with current guidelines. In the high risk group, nonsurgical endoscopic surveillance was performed in 20 (38.5 %) cases, representing potential under-treatment. After a median follow-up of 30 (6 – 130) months, no patients developed tumor recurrence. At multivariate analysis, age (OR 1.21, 95 %CI 1.02 – 1.42; P = 0.02) and CCI (OR 1.67, 95 %CI 1.12 – 3.14; P = 0.04) were independent predictors for subsequent surgery.Conclusions A substantial rate of inappropriate post-endoscopic treatment of pT1-CRC was observed when compared with current guidelines. This was apparently related to an overestimation of patient-related factors rather than endoscopically or histologically related factors.